The Influence of Arbuscular Mycorrhizal Fungi (FMA) Dosage and Yomari Liquid Organic Fertilizer on the Growth of Seedlings of Agarwood-Producing Plants (Aquilaria malacensis Lamk.) on Former Gold Mining Soil” - Satria, Benni; Martinsyah, Rachmad Hersi; Armansyah, Armansyah; Erona, Meisilva; Warnita, Warnita (International Journal of Environment, Agriculture and Biotechnology, 2023)
Former gold mining land exhibits poor soil fertility, both biologically, chemically, and physically due to the damaging effects of the mining process on the land. Marginal land conditions, like former gold mining areas, necessitate high-viability seedlings. Efforts to acquire quality seeds and boost the productivity of this land involve planting adaptable and high-quality plant seeds, such as the agarwood-producing plant (Aquilaria malaccensis Lamk.). This plant is among the adaptive non-timber forest products that grow and naturally produce without inoculation (injection) on ex-mining lands—gold, nickel, rocky sand, tin, and coal—supplemented with liquid organic fertilizers like Yomari and Arbuscular Mycorrhizal Fungi (AMF) on Aquilaria malaccensis Lamk plants. Yomari liquid organic fertilizer, with its high organic and nutrient content, can enhance soil organisms, improve soil pH, while AMF can promote root growth and expansion, aiding roots in water and nutrient absorption through their external hyphae. Consequently, this facilitates the production of numerous and robust roots. This research aims to determine the optimal interaction between AMF doses and Yomari Liquid Organic Fertilizer for the growth of Aquilaria malaccensis Lamk seedlings in former gold mining land. Additionally, it seeks to ascertain the impact of administering the best Yomari organic fertilizer dosage and the best AMF dosage on the growth of Aquilaria malaccensis Lamk on ex-gold mining land. This research was conducted from June to November 2022 in the nursery of the Faculty of Agriculture, Andalas University. Employing a factorial experimental method in a Completely Randomized Design (CRD) with two factors—firstly, the AMF dose consisting of four levels: 10 grams (F1), 20 grams (F2), 30 grams (F3), and 40 grams (F4), and secondly, the Yomari organic fertilizer dosage comprising five levels: 0 ml (Y0), 0.75 ml/l (Y1), 1.5 ml/l (Y2), 2.25 ml/l (Y3), and 3.0 ml/l (Y4)—each treatment level comprised four replications. Qualitative and quantitative observation data were analyzed using the F-test at a 5% level of significance. Post-hoc analysis for differences among treatments was conducted using the BNT test at the 5% level. Observations included the percentage of live seeds, seed height increment, leaf number, widest leaf width, root weight, and percentage of roots infected by AMF in ex-gold mining soil media inoculated with Acaulospora sp. and Gigaspora sp. The administration of 40 grams of FMA with a dose of 3.00 ml/l of liquid organic fertilizer showed an increase in the percentage of survival, an increase in the number of leaves, an increase in the height of the plant seedlings, the widest leaf width, the percentage of root weight, and the seedlings of agarwood-producing plants infected with AMF.